Fatty Acids Synthesized from Hexadecane by Pseudomonas aeruginosa - Romero, Ethel M. (1966)
The lipids extracted from Pseudomonas aeruginosa incubated with hexadecane in a mineral medium were separated into a nonpolar and three polar fractions by thin-layer chromatography. The fatty acid composition of the four cellular fractions and that of the lipids excreted into the medium was studied by gas-liquid chromatography. Saturated fatty acids with 14 to 22 carbons were recognized, together with monoenoic, dienoic, and hydroxylated acids. Hydroxylated fatty acids were principally found in two polar fractions containing rhamnose and glucose; the other polar fraction, containing serine, alanine, ethanolamine, and leucine, was richer in monoenoic fatty acids. Octadecadienoic acid was found in the neutral fraction.